Identifikasi Peran UPT. Malioboro terhadap Penyandang difabel di Kawasan Malioboro, Yogyakarta (Analisis SOAR) - Pasaribu, Asdalia Br; Suryasih, Ida Ayu (JURNAL DESTINASI PARIWISATA; Vol 8 No 2 (2020): VOL 8, NO 2 (2020): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2020.v08.i02.p13, 2020)
This research background is the presence of persons with diffability in the Malioboro area who have not benefited from tourism activities , so that make people with diffability only show their limitations,  in addition  the difficulties  for persons with diffability have an impact on their  welfare. The Yogyakarta Government has an ambition to make Yogyakarta as an accessible city, to realizing that, the Malioboro Technical Implementation Unit has the duty to empower the community in the  Malioboro area according to its role.The objectives of this study are : 1) How the role of the involvement of Malioboro Technical Implementation Unit for People with diffability  and 2) What is the strategy of empowering people with diffability by stakeholders in the Malioboro tourism area. The analysis in this study is a descriptive qualitative analysis in reviewing the role of a technical unit to manage the  Malioboro area, called  Unit Pengelola Teknis (UPT) Malioboro involved in existing conditions and SOAR analysis of identified strengths, opportunities, expectations and results to be achieved. This research located in the Malioboro area, there is  a lot of people with diffability who have not paid enough attention to location.The results of the study show that the Malioboro Technical Implementation Unit has not carried out its duties in the field of empowerment and taking care of the of people with diffability.  The involvement is considered low, in addition,  the research indicates that many persons with diffability hope to be accommodated to receive the same tourism benefits, and are expected to be strongly involved in the future.   Keyword :  Diffability, Empowerment, Technical Implementation Unit Malioboro